Functional diversity supports the physiological tolerance hypothesis for plant species richness along climatic gradients. (8th January 2014) - Spasojevic, Marko J.; Grace, James B.; Harrison, Susan; Damschen, Ellen I.; Salguero‐Gómez, Roberto
Summary The physiological tolerance hypothesis proposes that plant species richness is highest in warm and/or wet climates because a wider range of functional strategies can persist under such conditions. Functional diversity metrics, combined with statistical modelling, offer new ways to test whether diversity–environment relationships are consistent with this hypothesis. In a classic study by R.H. Whittaker (Ecological Monographs, 1960), herb species richness declined from mesic (cool, moist, northerly) slopes to xeric (hot, dry, southerly) slopes. Building on this data set, we measured four plant functional traits (plant height, specific leaf area, leaf water content and foliar C:N) and used them to calculate three functional diversity metrics (functional richness, evenness and dispersion). We then used a structural equation model to ask whether 'functional diversity' (modelled as the joint responses of richness, evenness and dispersion) could explain the observed relationship of topographic climate gradients to species richness. We then repeated our model examining the functional diversity of each of the four traits individually. Consistent with the physiological tolerance hypothesis, we found that functional diversity was higher in more favourable climatic conditions (mesic slopes) and that multivariate functional diversity mediated the relationship of the topographic climate gradient to plant species richness. We found similar patterns for models focusing on individual trait functional diversity of leaf water content and foliar C:N. Synthesis. Our results provide trait‐based support for the physiological tolerance hypothesis, suggesting that benign climates support more species because they allow for a wider range of functional strategies.